Deconstructing the Body: Transgender and Intersex Identities and Sex Discrimination – The Need for Strict Scrutiny - Ezie, Cinyere (Columbia Journal of Gender and Law, 2011)
Sex is documented, administered, and adjudicated via a network of statutes, regulations, and administrative rules that is astonishing for both its inconsistencies and its complexity.’ Courts and agencies tasked with issuing identity documents, or determining who qualifies as a spouse for the purposes of marriage licenses or same-sex marriage bans, routinely adjudicate the question of sex-employing “common sense” approaches to determine whether a person is “male” or “female.” For transgender persons seeking new drivers’ licenses or other forms of official recognition, the folkways of sex can be particularly dire because courts have naturalized both the idea of binary sex and the impossibility of sex reassignment. In refusing to recognize a transgender woman as a legal woman, a Texas appeals court exclaimed, “There are some things we cannot will into being. They just are.”‘ The Kansas Supreme Court followed suit, stating: “[W]e recognize that J’Noel has traveled a long and difficult road. J’Noel has undergone electrolysis, thermolysis, tracheal shave, hormone injections, extensive counseling, and reassignment surgery. Unfortunately, after all that, J’Noel remains a transsexual, and a male. “